The impact of sport on psychmotor development of adolescents - Radončić Mirza; Šabanović Binasa (Univerzitetska Misao)
Psychomotor development provides numerous essential skills for the success of children and adolescents in later life. Participation in sports is crucial for proper growth and development during adolescence. This research was conducted with the aim of examining the impact of sports on the psychomotor development of adolescents. The study was carried out at the "12. December" Elementary School in Sjenica, with a sample of 80 respondents aged 12 to 14 years, with both genders represented equally in terms of number and age. In line with the research problem and objectives, we applied the Psychomotor Evaluation Test, created as a measurement instrument based on Oliveira's test (Oliveira, 2008). The psychomotor tests evaluated five psychomotor abilities: coordination and balance (CB), body composition (BC), laterality (L), spatial organization (SO), and temporal organization (TO). In the coordination section, we focused on global coordination, dissociative movements, and hand-eye coordination, which involves coordinated control of eye movements by hand movements and the processing of visual input to guide reach and grasp, along with the use of proprioception of the hands to guide the eyes. For balance, we studied both its static and dynamic characteristics. Over a period of 4 weeks, a structured physical education class plan was implemented. The physical education teacher led only the experimental group through these lessons, which were pre-structured, planned, and tailored for the experimental group. Students in the experimental group participated in regular physical education classes four times a week, each lasting 45 minutes. The experimental group completed a total of sixteen physical education classes. At the end of the research, the same group of tests was applied to both groups. Growth in psychomotor characteristics was consistently statistically higher in the experimental group. Based on the results, we conclude that there were no significant deviations based on gender. The research demonstrated the impact of physical activity on the psychomotor and overall development of adolescents.